Occlusion dysfunction and Alzheimer’s disease: Mendelian randomization study - Wang, Qing; Zhen, Wenyu; Hu, Rui; Wang, Zifei; Sun, Yuqiang; Sun, Wansu; Huang, Chunxia; Xu, Jianguang; Zhang, Hengguo (Frontiers in Aging Neuroscience, 2024)
Aim Occlusion dysfunction (OD) is increasingly linked to Alzheimer’s disease (AD). This study aimed to elucidate the causal relationship between OD and AD using Mendelian randomization (MR) analysis. Materials and methods Genome-wide association study (GWAS) meta-analysis data obtained from FinnGen, IEU Open GWAS, and UK Biobank (UKBB) was represented as instrumental variables. We validated the causal relationship between periodontal disease (PD), loose teeth (PD & occlusion dysfunction), dentures restoration (occlusion recovery), and AD. Results According to the MR analysis, PD and AD have no direct causal relationship (P = 0.395, IVW). However, loose teeth significantly increased the risk of AD progression (P = 0.017, IVW, OR = 187.3567, 95%CI = 2.54E+00−1.38E+04). These findings were further supported by the negative causal relationship between dentures restoration and AD (P = 0.015, IVW, OR = 0.0234, 95%CI = 1.13E-03−0.485). Conclusion The occlusion dysfunction can ultimately induce Alzheimer’s disease. Occlusion function was a potentially protective factor for maintaining neurological health.